2015
DOI: 10.1371/journal.pone.0117046
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-Like Growth Factor 1, Glycation and Bone Fragility: Implications for Fracture Resistance of Bone

Abstract: Despite our extensive knowledge of insulin-like growth factor 1 (IGF1) action on the growing skeleton, its role in skeletal homeostasis during aging and age-related development of certain diseases is still unclear. Advanced glycation end products (AGEs) derived from glucose are implicated in osteoporosis and a number of diabetic complications. We hypothesized that because in humans and rodents IGF1 stimulates uptake of glucose (a glycation substrate) from the bloodstream in a dose-dependent manner, the decline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 55 publications
0
18
0
3
Order By: Relevance
“…IGF-I is also synthesized by osteoblasts and it is a regulator of bone cells metabolism [34]. Several studies showed a reduced IGF-1 activity when glucose and AGEs levels are high, suggesting an osteoblastic resistance to IGF-1 effects [35, 36].…”
Section: Potential Pathophysiological Basis Of the Increased Fractmentioning
confidence: 99%
See 1 more Smart Citation
“…IGF-I is also synthesized by osteoblasts and it is a regulator of bone cells metabolism [34]. Several studies showed a reduced IGF-1 activity when glucose and AGEs levels are high, suggesting an osteoblastic resistance to IGF-1 effects [35, 36].…”
Section: Potential Pathophysiological Basis Of the Increased Fractmentioning
confidence: 99%
“…A recent review evaluating the risk of fall-related fracture in T2DM subjects on sulfonylureas concluded that available studies suffer methodological limitations and may have underestimated the risk [80, 81]. Further studies are needed to define the effect of these drugs on falls and fractures, although the overall beneficial effects of this class of drugs are currently debated [34, 82]. …”
Section: Effects Of Hypoglycaemic Drugs On Bone Metabolism and Framentioning
confidence: 99%
“…In animal models of type 2 diabetes mellitus (WBN/Kob rats), the appearance of hyperglycemia coincides with the increase of non-enzymatic cross-links (pentosidine) and the reduction of bone strength[23]. In support of these data, there is also evidence of the effects of advanced glycation end products as mechanisms for the emergence of osteoporosis in clinical investigations[24]. In the present study we observed a positive correlation of HbA1c and serum glucose levels with BMAT, suggesting another potential mechanism for bone weakening related to hyperglycemia.…”
Section: Discussionmentioning
confidence: 99%
“…IGF-1, highly expressed in osteoblast and chondrocytes [34], exhibits its bone anabolic effect through promoting osteoblasts differentiation and bone mineralization [35]. Deficiency of IGF-1 in the course of diabetes may contribute to skeletal abnormalities and lead to impaired bone formation, and increased bone fragility [36]. Clinically, serum level of IGF-1 is positively associated with increased bone mass [37] and inversely associated with the number of vertebral fractures in postmenopausal women with T2DM [5, 38].…”
Section: Discussionmentioning
confidence: 99%